New Regulatory Roles of Galectin-3 in High-Affinity IgE Receptor Signaling - Bambouskova, Monika; Polakovicova, Iva; Halova, Ivana; Goel, Gautam; Draberova, Lubica; Bugajev, Viktor; Doan, Aivi; Utekal, Pavol; Gardet, Agnes; Xavier, Ramnik J; Draber, Petr (Molecular and cellular biology, 2016)
Aggregation of the high-affinity receptor for IgE (FcεRI) in mast cells initiates activation events that lead to degranulation and release of inflammatory mediators. To better understand the signaling pathways and genes involved in mast cell activation, we developed a high-throughput mast cell degranulation assay suitable for RNA interference experiments using lentivirus-based short hairpin RNA (shRNA) delivery. We tested 432 shRNAs specific for 144 selected genes for effects on FcεRI-mediated mast cell degranulation and identified 15 potential regulators. In further studies, we focused on galectin-3 (Gal3), identified in this study as a negative regulator of mast cell degranulation. FcεRI-activated cells with Gal3 knockdown exhibited upregulated tyrosine phosphorylation of spleen tyrosine kinase and several other signal transduction molecules and enhanced calcium response. We show that Gal3 promotes internalization of IgE-FcεRI complexes; this may be related to our finding that Gal3 is a positive regulator of FcεRI ubiquitination. Furthermore, we found that Gal3 facilitates mast cell adhesion and motility on fibronectin but negatively regulates antigen-induced chemotaxis. The combined data indicate that Gal3 is involved in both positive and negative regulation of FcεRI-mediated signaling events in mast cells.
Keywords: galektin 3; Calcium; receptory IgE; Actins; Lysosomes; Mast Cells; High-Throughput Nucleotide Sequencing; vápník; fosforylace; Receptors, IgE; cytokiny; signální transdukce; Phosphorylation; myši inbrední BALB C; Galectin 3; Ubiquitination; ubikvitinace; aktiny; prostaglandin D2; Signal Transduction; Mice, Inbred BALB C; buněčná adheze; lyzozomy; RNA, Small Interfering; Animals; malá interferující RNA; mastocyty; zvířata; vysoce účinné nukleotidové sekvenování; Cytokines; Chemotaxis; chemotaxe; Cell Adhesion; Prostaglandin D2